Training and load control after the Achilles tendon injury in a volleyball player, part 3 (Revista científica Olimpia, 2026)
The objective was to explain the final phase of the periodized training in 2019 and 2020 after the Achilles tendon injury and how the training load was controlled from 2014 to 2020. The subject of the study was a volleyball player that was of the study of Marques Junior and Barbosa (2016). This article is the part 3, presenting the periodized training from 2019 and 2020 that used the specific periodization for the volleyball. In this work, it was presented the control of the periodization training load from 2014 to 2020, the trainer practiced the training load control through of the internal load, quantity of training and rest, quantity of training types, exercises performed, abdominal circumference, and vertical jump. In conclusion, periodized training with adequate control of the training load is essential to provide an improvement in the physical preparation of a volleyball player that had a partial rupture in the right Achilles tendon.
Keywords: injury; sport; rupture; tendon; training; training load.